Sustainable packaging: A comparative study on thermoplastic whey protein films with biodegradable plasticizers - Forough Abbasi Shahir; Zahed Ahmadi; Sayed Mahmood Rezaee Darvishi (eXPRESS Polymer Letters)
Glyceryl lactate (GlyLA) was synthesized through the esterification of glycerol (Gly) and lactic acid (LA) to plasticize whey protein concentrate (WPC) films with three different ratios of WPC to plasticizer (85, 90, and 100% w/w). LA was also introduced as a new plasticizer of whey protein films and compared in similar contents. Gly-plasticized films were also used as control groups. The synthesized GlyLA, including compatible esterification degree with WPC, was characterized by Fourier transform infrared Spectroscopy (FTIR) and hydrogen nuclear magnetic resonance spectroscopy (H-NMR) analyses. Then, the plasticizing effect of different types of plasticizers on the optical, thermal, mechanical, and water resistivity properties of the prepared films was evaluated. FTIR in attenuated total reflectance (ATR), Differential Scanning Calorimetry (DSC), tensile measurements, and cup method were also employed to examine the molecular structure, transition temperatures, mechanical resistivity, and water vapor permeability (WVP) of the modified films. The results showed a lower glasstransition temperature (Tg) and better ductility. By Increasing plasticizer content, solubility and WVP were increased in all groups. Furthermore, WPC-based films plasticized with 80 or 90% w/w of LA and GlyLA exhibited not only higher tensile strength and flexibility but also remarkably lower WVP than Gly plasticized films, turning them into potential alternatives for application as food packaging.